IMPLEMENTASI MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN CREATIVE THINKING SISWA PADA MATERI MENGUBAH BENTUK ENERGI KELAS IV SD NAMIRA KRAKSAAN - Ridha Ashari, Ahmad; Arya Wardana, Ludfi; Hattarina, Shofia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low creative thinking ability of fourth-grade students at SD Namira Kraksaan on the topic of energy transformation. The purpose of this study was to determine the implementation of the Project Based Learning (PjBL) model in improving students’ creative thinking abilities. This study employed a Classroom Action Research (CAR) approach using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection stages. The research subjects were 25 students of class IV A at SD Namira Kraksaan. Data collection techniques included observation, interviews, tests, and documentation. The research instruments consisted of observation sheets, interview guidelines, and pretest and posttest questions on creative thinking skills. The results showed that the implementation of the Project Based Learning (PjBL) model was able to improve students’ creative thinking abilities. This improvement was indicated by the increase in students’ average scores from the pretest score of 36.7 with a mastery percentage of 16%, to 58.7 in the cycle I posttest with a mastery percentage of 40%, and further increased to 70.4 in the cycle II posttest with a mastery percentage of 88%. In addition, students became more active in discussions, more confident in expressing ideas, and more capable of producing creative answers and products. Therefore, the Project Based Learning (PjBL) model proved effective in improving students’ creative thinking abilities on the topic of energy transformation in fourth-grade students at SD Namira Kraksaan.